(untitled) (Nepalese Journal of Radiology, 2012)
Acute or subacute myelopathy with spontaneous thrombosis of the veins in a patient with a spinal arteriovenous malformation (AVM) has been referred to as "Foix-Alajouanine syndrome (FAS)". A previously healthy 35-year-old man developed neurological illness with progressive lower extremity weakness and low back pain. MRI demonstrated diffuse swelling of the thoracic spinal cord, suggesting myelopathy with few intradural extramedullary serpeginous flow voids. We report a case of Foix-Alajouanine syndrome with a review of the literature. DOI: http://dx.doi.org/10.3126/njr.v1i1.6319 Nepalese Journal of Radiology Vol.1(1): 27-29